Rationalizable partition-confirmed equilibrium - Yuichiro Kamada; Drew Fudenberg (Theoretical Economics, 2015)
Rationalizable partition-confirmed equilibrium (RPCE) describes the steady state outcomes of rational learning in extensive-form games, when rationality is common knowledge and players observe a partition of the terminal nodes. RPCE allows players to make inferences about unobserved play by others. We discuss the implications of this using numerous examples, and discuss the relationship of RPCE to other solution concepts in the literature.
Keywords: C72; 330; Rationalizablity; common knowledge; extensive-form games; self-confirming equilibrium